Is Zimbabwe's education system disaster-ready? Evaluating risk reduction strategies in Binga district schools - Lunga, Wilfred; Ziweya, Mildred; Kaifa, Jane M.; Musarurwa, Charles; Magampa, Mmakotsedi; Baloyi, Caiphus; Moyo, Annah (Frontiers in Sustainability, 2025)
Building on the 2006 Disaster Risk Reduction Begins at School campaign by the International Strategy for Disaster Reduction (ISDR), this study examines the role of formal education in enhancing hazard awareness and disaster preparedness among learners in Binga district, Zimbabwe a region that is highly exposed to recurring climate-induced hazards. Despite the implementation of various school-based DRR awareness and training initiatives, their efficacy remains largely unverified through empirical research. This study adopts a qualitative research design, utilizing a structured questionnaire administered to learners aged 8–18 across 20 primary and secondary schools. Key indicators assessed include disaster knowledge, hazard education participation, preparedness levels, risk perception, and community engagement. A two-tier cluster sampling strategy stratifying Binga into northern and southern zones was employed to ensure geographical representation. Findings reveal that current DRR education initiatives are inadequate in cultivating comprehensive disaster resilience among learners. The study calls for targeted programmatic improvements, including curriculum integration, teacher capacity development, and stronger school-community DRR linkages.